Template-Assisted Self-Assembly of Conductive Polymer Electrodes for Ionic Electroactive Polymers - Jo, Andrew; Huet, Clémence; Naguib, Hani E. (Frontiers in Bioengineering and Biotechnology, 2020)
Ionic electroactive polymers (ionic EAPs) can greatly aid in biomedical applications where micro-sized actuators are required for delicate procedures. Since these types of actuators generally require platinum or gold metallic electrodes, they tend to be expensive and susceptible to delamination. Previous research has solved this problem by replacing the metallic electrodes with conductive polymers (CP) and forming an interpenetrating polymer network (IPN) between the conductive polymer (CP) and the solid polymer electrolyte (SPE). Since these actuators contain toxic ionic liquids, they are unsuitable for biological applications. In this study, we present a novel and facile method of fabricating a biocompatible and ionic liquid-free actuator that uses semi-IPN to hold the CP and Nafion-based SPE layers together. Surface activated fabrication treatment (SAFT) is applied to the precursor-Nafion membrane in order to convert the sulfonyl fluoride groups on the surface to sulfonate. Through template-assisted self-assembly, the CP electrodes from either polyaniline (PANI) or poly(3,4-ethylenedioxythiophene) (PEDOT) interlock with the surface treated precursor-Nafion membrane so that no delamination can occur. The electrodes growth pattern, interfacial layer’s thickness, and shape can be controlled by adjusting the SAFT concentration and duration.